SOLVING EXPERIMENTAL PROBLEMS IN PHYSICS TEACHING IN A SECONDARY SCHOOL - Muzaffar Sattikulov; Ruzibu Erkamovna Khalilova (European Science Publishing, 2024)
This article examines the problem of improving the methodology of teaching physics in secondary schools by solving experimental problems in optics. By solving a number of experimental problems, some methods of studying optics were identified. An empirical solution to the experimental problems is shown.
Keywords: Experiment, task, optics, quantity, quality, experience, light, beam.